Tingkat Kepuasan Kerja Karyawan Ditinjau dari Work Life Balance di PT PLN (Persero) UP3 Bojonegoro - Sarwendah, Retno Gandhes; Fiernaningsih, Nilawati (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze employee job satisfaction based on work-life balance at PT PLN (Persero) UP3 Bojonegoro. This research employs a qualitative method, involving seven permanent employees of PT PLN (Persero) UP3 Bojonegoro as the research subjects. Data collection techniques include observation, interviews, and documentation. Data analiysis follows the interactive model by Miles and Huberman, comprisisng data collection, data reduction, data display, and conclusion drawing. The redults indicate that employee job satisfaction, as viewed from the perspective of work life balance, falls into a satisfying catefory. Work life balance plays a role in enhancing employee job satisfaction. The novelty of this research lies in its focus on how work life balance can implove job satisfacation.